A mobile video intervention for women's health of North Korean defectors. Issue 6 (27th September 2018) - Lee, Min Kyeong; Shin, Gisoo
Abstract: Background: The prevalence of North Korean female defectors is increasing in South Korea. Women who leave North Korea are exposed to sexual harassments, abuse, and other threats to their survival, which can have a devastating effect on their health. Aims: In this study, a mobile video intervention program about selected aspects of women`s health was developed specifically for North Korean female defectors; its impact on behavioral change was evaluated. Methods: A one group pre/posttest design was used with 61 female defectors who participated in the mobile video intervention. The program consisted of eight sessions focusing on the prevention and management of vaginitis and cervical cancer. Results: The study results showed that knowledge and behavioral confidence on vaginitis and cervical cancer increased significantly among the participants following the intervention. Conclusions: This mobile video intervention program was effective in improving specific health knowledge and behavioral confidence of the participants. The program can be used to improve women`s health in this population.